Ammonia emissions from combustion in gasoline engines - Bajwa, A; Shankar, V; Leach, F (SAE International, 2023)
Forthcoming worldwide emissions regulations will start regulating ammonia emissions from light duty vehicles. At present, most light duty vehicles are powered by gasoline spark ignition engines. Sources of ammonia emission from such engines can be in-cylinder reactions (i.e. combustion) or downstream reactions across aftertreatment devices, particularly three-way catalysts. The latter has been known to be a major source of ammonia emissions from gasoline vehicles and has been extensively investigated. The former (combustion), less so, and thus is the subject of this work. A two-zone thermodynamic spark ignition engine model with a comprehensive chemical kinetics framework (C3MechV3.3 mechanism), after being validated against experimental ammonia emissions data, is used to study ammonia formation during combustion. Reaction pathways responsible for its generation are analysed and the effects of changing the following engine operational and combustion parameters are explored: engine load, start of combustion, combustion duration, fuel-air equivalence ratio, and exhaust gas recirculation fraction. Ammonia production was found to be slower than that of other major pollutant species - starting late during the heat release stage, peaking around the time when the cylinder pressures and temperatures were at their highest, and having a late, prolonged production stage after the end of heat release. Ammonia concentrations did not ‘freeze’ until late into the expansion process. Initial ammonia production was driven by three body elementary reactions involving hydrogen radicals produced from the fuel oxidation/reduction, and the late-stage production was dominated by H2O reactions with amino radicals. The net effect of these production pathways on ammonia emissions in response to changes in engine operation was non-monotonic and depended on the dominant pathway at the particular thermal conditions. However, overall trends suggested that emissions increased when engine load increased, combustion duration shortened, combustion timing advanced, fuel-air mixture became richer and exhaust gas recirculation fraction decreased.